Timing of Acupuncture during LTP-Like Plasticity Induced by Paired-Associative Stimulation - Xiao-kuo He; Qian-qian Sun; Hui-hua Liu; Xin-yi Guo; Cheng Chen; Li-dian Chen (Behavioural Neurology)
The aim of this study was to investigate the time-dependent effects of acupuncture on the excitability and long-term potentiation- (LTP-) like plasticity induced by paired-associative stimulation (PAS) over the primary motor cortex (M1). The present examination is the first to report the influence of acupuncture on the motor-evoked potential (MEP) throughout the treatment process, including baseline (before acupuncture), the needle in situ, and the needle removal. Subsequently, the LTP-like plasticity induced by paired-associative stimulation (PAS) was explored, which consisted of 200 pairs of electrical stimulation of the ulnar nerve at the first dorsal interosseous (FDI), followed by transcranial magnetic stimulation (TMS) over the bilateral M1. TMS-MEP amplitudes over the bilateral M1 in resting conditions were measured throughout the whole treatment process. Finally, we confirmed the behavioral measurements. Significant changes were found in both the contralateral and ipsilateral acupuncture sizes as compared to the baseline values. Our results indicated that acupuncture modulated the excitability of M1, and the synaptic plasticity was time-dependent. We concluded that acupuncture should be combined with rehabilitation techniques to improve the motor function in stroke patients. Therefore, we put forward the combined application of the acupuncture timing and rehabilitation for higher therapeutic effectiveness. This trial was registered in the Chinese Clinical Trial Registry (registration no. ChiCTR-IPR-1900020515).